2003
DOI: 10.1128/aac.47.8.2649-2654.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Release of Pneumolysin by Streptococcus pneumoniae In Vitro and In Vivo after Treatment with Nonbacteriolytic Antibiotics in Comparison to Ceftriaxone

Abstract: Pneumolysin, a virulence factor of Streptococcus pneumoniae with cytotoxic and proinflammatory activities, occurs at concentrations from 0.85 to 180 ng/ml in cerebrospinal fluid (CSF) of meningitis patients. In pneumococcal cultures and in a rabbit meningitis model, the concentrations of pneumolysin in supernatant and CSF were lower after addition of nonbacteriolytic bactericidal antibiotics (rifampin and clindamycin) than after incubation with ceftriaxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
99
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 31 publications
5
99
1
4
Order By: Relevance
“…Although pneumolysin is located in the cytoplasm of S. pneumoniae, it is steadily released into the culture medium during growth in vitro, either through a basal level of autolysis (37) or via a yet to be characterized export mechanism (38). Free pneumolysin has also been detected in vivo during experimental infections (39). By binding C1q, pneumolysin, rather than inhibit the classical pathway, may actually increase complement activity, and how it is able to prevent complement deposition on S. pneumoniae is unclear at present.…”
Section: Discussionmentioning
confidence: 99%
“…Although pneumolysin is located in the cytoplasm of S. pneumoniae, it is steadily released into the culture medium during growth in vitro, either through a basal level of autolysis (37) or via a yet to be characterized export mechanism (38). Free pneumolysin has also been detected in vivo during experimental infections (39). By binding C1q, pneumolysin, rather than inhibit the classical pathway, may actually increase complement activity, and how it is able to prevent complement deposition on S. pneumoniae is unclear at present.…”
Section: Discussionmentioning
confidence: 99%
“…LAGROU et al [19] also reported that sub-MIC of erythromycin reduced the haemolytic activity of PLY by MRSP. SPREER et al [21] reported that in comparison to standard therapy with ceftriaxone, protein synthesis inhibitors such as rifampin and clindamycin reduced the release of PLY by S. pneumoniae in human cerebrospinal fluid during therapy of pneumococcal meningitis. The present results are in agreement with those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, pneumococci were lysed with protease inhibitor cocktails (Nacalai Tesque, Kyoto, Japan) with a sonicator (Ultrasonic Disruptor UD-201: Tomy Seiko, Tokyo, Japan) [20]. The western blot procedure for PLY was then performed as described previously [21]. Sample proteins (30 mg) of whole lysates were separated using SDS-PAGE (sodium dodecyl sulphate-polyacrylamide gel electrophoresis) and transferred onto nitrocellulose membranes.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In the present study, we investigated the effects of exposure of isolated human neutrophils to pneumolysin, at concentrations of 5-20 ng?mL -1 , in the presence and absence of the chemoattractant f-MLP on the release of MMP-8 and -9. Pneumolysin concentrations of up to 9 mg?mL -1 and 180 ng?mL -1 have been detected in pneumococcal culture fluids in vitro and in the cerebrospinal fluid of patients with pneumococcal meningitis, respectively [23,24]. N-formylated polypeptide chemoattractants are produced by the pneumococcus [25,26], and may act in concert with pneumolysin to augment the pro-inflammatory activities of neutrophils, as well as those of monocytes/ macrophages [4].…”
Section: Discussionmentioning
confidence: 99%